GEDUNG PERTUNJUKAN SENI AUDIO VISUAL DI PONTIANAK DENGAN PENDEKATAN FOLDING ARCHITECTURE - Amelia Putri Sukmawan; Tri Wibowo Caesariadi; Uray Fery Andi (JMARS: Jurnal Mosaik Arsitektur, 2022)
Audio-visual art is an art that combines motion, tone, and visuals that is received by senses of sight and hearing, such as dance, music, and theater. The existence of dance, music, and theater arts in Pontianak is still anticipated by society with more than 1,000 visitors to the Taman Budaya Pontianak per month, but it can’t accomodate people on large capacity. Art makes artist want to express their works through a performance, this triggers the need for a new art building in Pontianak to support art performance activities for artists. The design of the Auditory Visual Art Center in Pontianak is located on Jalan M. Sohor using five stages design methods that contain ideas, information, analysis, synthesis, evaluation, and optimization. The function of the Auditory Visual Art Center in Pontianak is divided into three, namely primary as performances and rehearsals, secondary as commercial and public facilities, and supporting as management. The design implements folding architecture approach which have the same characteristics as art that reflects a form of creativity, flexibility, and dynamics. The result design of Auditory Visual Art Center in Pontianak is consisting one building mass with three section of areas, which called area of artists, performances, and management.